Fabeldyr i udvikling: En analyse af D-brakteaterne - Carlsen, Elisabeth Barfod (Hikuin, 2002)
The Evolution of Fabulous Beasts An analysis of the D-bracteates By Elisabeth Barfod Carlsen The D-bracteates, the subject of this paper, constitute more than a third of the whole corpus of Migration-period bracteates and thus are the second largest group after the C-bracteates. The design of the D-bracteates comprises one or more animals in the early Germanic animal style. As these motifs are distant from the original models of the bracteates, on Late-Roman coins and gold medallions, they have often been ignored in bracteate studies. The objective is to show that the D-bracteates were produced and deposited during a longer period than previously thought, and that the production of D-bracteates should not be regarded as merely a post-script to that of the other types. Migration-period bracteates in Denmark and Sweden have virtually all been found in hoards that can be interpreted as either votive or secular. Because of the great uncertainty over the date of deposition, hoards are not ideal for chronological studies. More than 20 per cent of the total number of D-bracteates have been found outside of Scandinavia (fig. 1). Many of these come from well-dated graves with rich artefact assemblages. The finds have been recorded in accordance with the catalogue and series of Karl Hauck et al., where all of the bracteates are photographed and drawn in a common style that does them justice. For the stylistic analysis of the D-bracteates the computerized dataprocessing method of correspondence analysis was used. The seriation that resulted is interpreted as a sequence of production that reflects the development of the style elements. The analysis comprised 174 specimens from Sweden and Denmark involving 85 different dies (fig. 2). »Production group« is abbreviated Pg. The seriation yields five usable groups (Pg. D I – D V). There is also a minor regional production group (Pg. D VI) which can be linked to the seriation on stylistic grounds. The selected bracteates of figure 3 only represents examples of the groups (App.). Thirty-nine different D-bracteate dies distributed amongst 66 specimens have been found outside of Denmark and Sweden. The seriation of the southern Scandinavian D-bracteates is used as the reference point for D-bracteates found outside of Scandinavia (fig. 4). This reveals whether these D-bracteates belong to the Scandinavian tradition or were locally made copies. In the finds from the Continent and England a new group appears with only one representative in southern Scandinavia: the local group from Kent, Pg. D V, which has much in common with Pg. D IV. What distinguishes this sequence of the D-bracteates from earlier schemes is the order of the groups. Previous scholars have regarded the bracteate design as having emerged fully formed, subsequently to degenerate. My seriation shows that the opposite is the case (fig. 5). The »degenerate« examples represent the inception of production, and the bracteates with the »optimal« designs represent its end. In relation to earlier bracteate specialists’ conclusions, the stylistic evolution is turned on its head. A comparison between the earliest specimens, particularly Pg. D I, and contemporary animal art reveals a congruency with both the Nydam Style and early Style I (fig. 6). One must infer, therefore, that the production of D-bracteates began no later than the inception of Style I, around AD 450/475. The demise of production, Pg. D IV, shows a stylistic agreement with the latest dated objects in Style I such as the Overhornbæk brooch (fig. 7). D-bracteates found outside of southern Scandinavia are to be viewed in terms of their stylistic similarity to bracteates in the southern Scandinavian seriation. On the Continent there is a greater diversity of style, and here direct importation cannot explain what we find. The tendency is for greater stylistical similarity to occur the closer one is to southern Scandinavia. This similarity is also found in hoarding practice. In Anglo-Saxon England there is greater similarity to the D-bracteates of southern Scandinavia, although here the objects are deposited in graves. Pg. D V represents the adoption and development of the southern Scandinavian practice of producing D-bracteates. D-bracteates found outside of southern Scandinavia are often wear-marked in a way that reveals a considerable period of use before deposition. The chronological study assigns the deposition of D-bracteates found in this area to the period from AD 500 onwards. The find-circumstances do not at present allow them to be dated any earlier, and these examples either belong to or are copies of the later production groups (Pg. D III – D IV). In Anglo- Saxon England the earliest burials of D-bracteates in graves occur around AD 520/525. Production began in southern Scandinavia and then spread to southern German groups, both through imports and imitation, while both importation and the development of local production took place in England. The earliest date for the deposition of a Dbracteate is from the Års find, with a terminus post quem of AD 425. How far into the 6th century deposition continued in southern Scandinavia depends upon when Style II began to be predominant in the artefactual range. The deposition of D-bracteates outside southern Scandinavia continued considerably later than this, and the Rhenen grave may be the (or at least one of the) latest dated burials containing the D-bracteate design.